2021
DOI: 10.3389/fcimb.2021.685068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of floR Variants Associated With a Novel Tn4371-Like Integrative and Conjugative Element in Clinical Pseudomonas aeruginosa Isolates

Abstract: Florfenicol is widely used to control respiratory diseases and intestinal infections in food animals. However, there are increasing reports about florfenicol resistance of various clinical pathogens. floR is a key resistance gene that mediates resistance to florfenicol and could spread among different bacteria. Here, we investigated the prevalence of floR in 430 Pseudomonas aeruginosa isolates from human clinical samples and identified three types of floR genes (designated floR, floR-T1 and floR-T2) in these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Studies have shown that IS Kpn23 plays an important role in expression of bla BKC-1 of K. pneumoniae ( 51 , 105 ). The floR gene has been described for the small plasmid p1807 ( 106 ) of Glaesserella parasuis and on the multidrug resistance region of an incomplete Tn 4371 -like integrative and conjugative element (ICE) in the P. aeruginosa chromosome ( 107 ). The virB11 virulence gene in our strain was associated with IME and putative ICE with T4SS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IS Kpn23 plays an important role in expression of bla BKC-1 of K. pneumoniae ( 51 , 105 ). The floR gene has been described for the small plasmid p1807 ( 106 ) of Glaesserella parasuis and on the multidrug resistance region of an incomplete Tn 4371 -like integrative and conjugative element (ICE) in the P. aeruginosa chromosome ( 107 ). The virB11 virulence gene in our strain was associated with IME and putative ICE with T4SS.…”
Section: Discussionmentioning
confidence: 99%
“…The vancomycin resistance is positively regulated by the VanS kinase receptor that may be interacting with antimicrobial peptides and allowing vancomycin to bind to receptors [ 52 ]. Effects were not found in Pseudomonas aeruginosa , which can be explained by the multiple intrinsic and plasmid resistance mechanisms that this pathogen can exhibit [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2003 study by Ariane Toussaint et al, the biphenyl catabolic transposon Tn 4371 was thoroughly sequenced and analyzed, revealing its mosaic structure with multiple building blocks, and a new family of genomic island was proposed(8). Although Tn 4371 has never been proven to transfer conjugally, the designation of ICE Tn 4371 family has been used to include a growing number of ICEs (9) (10) (11) (12). Ohtsubo et al compared 112 related elements and showed that βγ-type ICEs (a sub group of Tn 4371 -related ICEs from β and γ-proteobacterial species) have distinct conserved structure and distinguishable from those from α proteobacteria (αI and αII types).…”
Section: Introductionmentioning
confidence: 99%